Experimental investigation of the role of rock fabric in gas generation and expulsion during thermal maturation: Anhydrous closed-system pyrolysis of a bitumen-rich Eagle Ford Shale. (May 2018) - Shao, Deyong; Ellis, Geoffrey S.; Li, Yanfang; Zhang, Tongwei
Highlights: Gold-tube isothermal pyrolysis was conducted on low-maturity Eagle Ford Shale. Role of rock fabric in gas generation and expulsion upon maturation was studied. Gases in pyrolysis of intact rock fabric samples are more comparable to natural gas. Gas retention and chemical fractionation in the shale is a function of maturity. Hydrocarbon expulsion efficiency is determined by fluid pressure and permeability. Abstract: Gold-tube pyrolysis experiments were conducted on miniature core plugs and powdered rock from a bitumen-rich sample of Eagle Ford Shale to investigate the role of rock fabric in gas generation and expulsion during thermal maturation. The samples were isothermally heated at 130, 300, 310, 333, 367, 400, and 425 °C for 72 h under a confining pressure of 68.0 MPa, corresponding to six levels of induced thermal maturity: pre-oil generation (130 °C/72 h), incipient oil/bitumen generation (300 and 310 °C/72 h), early oil generation (333 °C/72 h), peak oil generation (367 °C/72 h), early oil cracking (400 °C/72 h), and late oil cracking (425 °C/72 h). Experimental results show that gas retention coupled with compositional fractionation occurs in the core plug experiments and varies as a function of thermal maturity. During the incipient oil/bitumen generation stage, yields of methane through pentane (C1 –C5 ) from core plugs are significantly lower than those from rock powder, and gases from core plugs are enriched in methane. However, the differences in C1 –C5 gas yield and composition decrease throughout the oil generation stage, and by the oil cracking stage no obvious compositional difference in C1 –C5 gases exists. The decrease in the effect of rock fabric on gas yield and composition with increasing maturity is the result of an increase in gas expulsion efficiency. Pyrolysis of rock powder yields 4–16 times more CO2 compared to miniature core plugs, with δ 13 CCO2 values ranging from −2.9‰ to −0.6‰, likely due to carbonate decomposition accelerated by reactions with organic acids. Furthermore, lower yields of gaseous alkenes and H2 from core plug experiments suggest that the rock fabric plays a role in promoting hydrogenation reactions of alkenes.